Under new ownership : privatizing China's state-owned enterprises - Yusuf, Shahid; Nabeshima, Kaoru; Perkins, Dwight H. (Palo Alto, CA: Stanford University Press, 2006)
Drawing upon new firm-level survey data, this volume assesses how changes in the ownership structure of SOEs affect management, governance, innovation, and performance, comparing these SOEs to other types of firms in China.
A copublication of Stanford Economics and Finance, an imprint of Stanford University Press, and the World Bank."
Includes bibliographical references (p. [241]-264) and index.
oif 25/07/16
Loans
Keywords: Privatization